Drug-induced kidney injury in Chinese critically ill pediatric patients - Hu, Biwen; Ye, Ling; Li, Tong; Feng, Zeying; Huang, Longjian; Guo, Chengjun; He, Li; Tan, Wei; Yang, Guoping; Li, Zhiling; Guo, Chengxian (Frontiers in Pharmacology, 2022)
Background: Drug-induced acute kidney injury (DIKI) is a common adverse drug reaction event but is less known in pediatric patients. The study explored the DIKI in Chinese pediatric patients using the Pediatric Intensive Care database (PIC). Method: We screened pediatric patients with acute kidney injury (AKI) using the KDIGO criteria from the PIC and then assessed the relationship between their drugs and DIKI using the Naranjo scale. For the fifteen frequently used DIKI-suspected drugs, we divided patients into drug-exposed and non-exposed groups, using the outcome of whether DIKI was presented or not. Propensity score matching (PSM) was used to control for the effects of four confounders, age, gender, length of hospital stay, and major diagnosis. Unconditional logistic regression was used to identify statistically significant differences between the two groups. Results: A total of 238 drugs were used 1,863 times by the 81 patients with DIKI during their hospital stay. After screening the Naranjo scale to identify the top 15 suspected DIKI drugs with a high frequency of use, we found that furosemide injection (P=0.001), midazolam injection (P=0.001), 20% albumin prepared from human plasma injection (P=0.004), fentanyl citrate injection (P=0.001), compound glycyrrhizin injection (P=0.026), vancomycin hydrochloride for intravenous (P=0.010), and milrinone lactate injection (P=0.009) were associated with DIKI. Conclusions: In critically ill pediatric patients, DIKI is more likely to occur after using furosemide injection, midazolam injection, 20% albumin prepared from human plasma injection, fentanyl citrate injection, compound glycyrrhizin injection, vancomycin hydrochloride for intravenous, milrinone lactate injection.